Comparative Evaluation of Fuzzy Logic, Sliding Mode, and LQR Controllers for DC Motor Position Control - Minh-Thy Pham; Lam-Trong-Tuan Bui; Thi-Thanh-Hoang Le; Van-Bac Nguyen; Le-Khoi-Nguyen Cao; Le-Nhat-Minh Tran; Xuan-Manh Ngo; Phong-Luu Nguyen; Dinh-Phu Nguyen (Peneliti Teknologi Teknik Indonesia, 2026)
This paper presents a comparative evaluation of three advanced control strategies for DC motor position control, namely Fuzzy Logic Control (FLC), Sliding Mode Control (SMC), and Linear Quadratic Regulator (LQR). First, the mathematical model of the DC motor is derived from the electrical and mechanical dynamic equations. Based on this model, the three controllers are designed and implemented in MATLAB/Simulink and experimentally validated on a microcontroller-based platform under identical operating conditions. The comparative analysis is performed using quantitative performance indices, including settling time, overshoot, steady-state error, and control effort. Simulation and experimental results show that the SMC controller provides the best overall performance with fast convergence, high robustness, and small steady-state error, while the FLC approach achieves smoother responses with moderate transient performance. The LQR controller demonstrates rapid state regulation but produces larger transient peaks and higher control effort compared with the other methods. The results highlight the practical trade-offs among intelligent, robust, and optimal control strategies for low-cost DC motor position control applications.